Formulation of Notary's Right of Refusal In Criminal Case Examination Process - Nuarta, I Nengah; Sukedi, Mochamad (Westscience Press, 2025)
The notary is frequently a party to a dispute that occurs between the parties to the deed. For the parties, the notary drafts an official deed. Because of this requirement, the notary must have legal protection in the form of the right of renunciation. Law Number 30 of 2004 about the Notary Position (UUJN) and Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Notary Position (UUJN-P) (norm vacuum) do not, however, restrict the right of renunciation for notaries. This study employed normative legal research as its methodology. The findings of this dissertation research serve as the philosophical foundation for allowing a notary to decline to perform his duties in relation to notarial deed making as a public official, namely offering protection and assurances for the attainment of legal certainty. Adding guidelines for the legal protection of notaries in the UUJN is one way to standardize the notary's power of refusal in the course of law enforcement over notarial deeds pertaining to legal matters. Researchers provide a proposal with the formulation of norms that are made into additional paragraph (5) in Article 66 of the UUJN. According to the established norms, notaries who follow the law and ethical codes are protected from both civil and criminal prosecution while carrying out their official duties.